Multimedia applications for the hearing impaired - CZYŻEWSKI, Andrzej; SKARŻYŃSKI, Henryk (Archives of Acoustics, 2007)
Hearing impairment is one of the fastest growing diseases of modern society. Therefore it is very important to develop new methods for diagnosis and therapy of hearing disorders. Some of them were introduced to practice as a result of a co-operation between institutions mentioned in the header. The system for mass-scale hearing screening is one of multimedia programs for testing communication senses introduced by the authors. The further developments include among others an application of dithering theory to practical solutions for tinnitus patients and a method of fitting hearing aids employing soft computing. The implemented hearing diagnostic & therapy applications and systems with their underlying concepts are reviewed in this paper.